ANALISIS CERPEN “ROBOHNYA SURAU KAMI” KARYA A.A. NAVIS DALAM PERSPEKTIF POSMODERNISME LINDA HUTCHEON - Rudi Ekasiswanto (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2020)
This study aims to provide sympathetic insight for who are interested in short stories in Indonesia through the perspective of Linda Hutcheon historical postmodernism. Through this research, we can find a description of story facts and the ideas of the author that are realized through the center and the periphery, along with the contextualization aspects of the short story A.A. Navis’ Robohnya Surau Kami to nowadays society. This research also contributes to literary works appreciation to educational institutions, academics, the society of literary enthusiasts, and the wider community in the form of short story research with the perspective of Linda Hutcheon’s postmodernism so that it is expected to increase the quantity of practice in postmodernism studies. The methodology used in the short story Robohnya Surau Kami using Linda Hutcheon's postmodernist theory is a descriptive method of analysis, by describing the facts which are then analyzed. The analysis does not merely describe but also gives sufficient understanding and explanation. Robohnya Surau Kami by A. A. Navis is a monumental work A. A. Navis containing religious elements. In his work, A. A. Navis presents inner experiences about the concept of the religious life of small communities in Indonesia. This short story is an outstanding and popular work as it is considered as a rare religious literature; AA Navis does not merely tell about worship and devotion to God, but also humanitarian values in Indonesia loaded with caring and tolerance so that it is necessary to trace the facts of the story in the short story, identify the center and the periphery that triggers conflict, and the implications of its contextualization of society in the present.